Fairtrade certified in brazilian coffee sector: analysis and perspectives - Alvarenga, Rafael Pazeto; Arraes, Nilson Antonio Modesto (Coffee Science - ISSN 1984-3909, 2017)
This paper offers help to decision for the Brazilian’s fairtrade coffee stakeholders. It does a broad and current position about the scene of fairtrade certification in Brazilian coffee sector. It was developed through literature review and interviews in institutions related to certification in Brazil. It was developed through literature review and interviews in institutions related to certification in Brazil. Its main results indicate that: i) half of the farmers cooperatives in Brazil were certified between 2009 and 2015; ii) in a few cooperatives are concentrated the most of the coffee producers and most of the sales of fairtrade coffee; iii) Brazilian scientific research suggest that certification has contributed to the improvement of the property management and also to internationalization of the business; iv) international literature indicates advantages, but problems in the distribution of the benefits and also many where the certification’s impacts were derisory. Considering the global context of Brazilian coffee sector, still not possible to affirm whether fairtrade certification is or not achieving its goals.